Hurst exponent estimation, verification, portability and parallelization - Kussainov, A.S.; Kussainov, S.G. (Recent Contributions to Physics, 2015)
We present multiple software programs for the Hurst exponent calculations for a sample time series collected by a neutron monitor detectors array. The first application is carried out by the finite differences approach, using a spreadsheet-type application for a single one hour long data series; the second is a complete, one and a half week long, mathematical and graphical analysis of six acquisition channels in Matlab; the third and the fourth are the data file parser and analyzer in C/C++ compiler on Windows platform, and its modified Linux version for simultaneous, parallel computing on a virtual cluster of three machines. All applications produce the same results proving the codes’ validity and portability across the operational systems and software packages.